Psychosomatic Complications of Decreased or Impaired Generative Function in General Medical Patients (Review) - V. E. Medvedev (Архивъ внутренней медицины)
In 35-56 % of patients depression of varying severity was diagnosed, in 25-76 % — anxiety and psychosexual disorders, in 40 % — anxiety and depressive disorders, in in 50 % — adjustment disorders, to 9.5 % — suicidal thoughts and attempts. Anxiety, depressive, dysmorphic and psychotic spectrum disorders are identified in 75 % of women seeking medical care during the menopause.Psychopharmacotherapy in female patients includes modern antidepressants, anxiolytics, and antipsychotics, with an emphasis on good tolerability, compatibility with hormone therapy, and easy dosing.Psychotherapy, psychological support and psychocorrectional work can reduce the severity of anxiety and depressive symptoms and significantly increase the success of treatment procedures.